2000
DOI: 10.1097/00003246-200003000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of heme oxygenase induction in ischemic acute renal failure

Abstract: These findings indicate that the expression of HO-1 in the ischemic kidney may be critical in the recovery of renal cell function in this animal model. These findings also suggest that H0-1 induction may play an important role in conferring protection on renal cells from oxidative damage caused by heme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 45 publications
5
121
2
3
Order By: Relevance
“…Similar observations have been made for HO in ischemic acute renal failure (50) and for VEGF in experimental thrombotic microangiopathy (51); both genes are also target genes induced by HIF-1 activation. These observations indicate that, at least in the kidney, HIF-1 activation might result in an adaptive response to renal ischemia.…”
Section: Discussionsupporting
confidence: 81%
“…Similar observations have been made for HO in ischemic acute renal failure (50) and for VEGF in experimental thrombotic microangiopathy (51); both genes are also target genes induced by HIF-1 activation. These observations indicate that, at least in the kidney, HIF-1 activation might result in an adaptive response to renal ischemia.…”
Section: Discussionsupporting
confidence: 81%
“…Although iCORM-3 was able to increase the levels of HO-1, it did not offer significant protection against ischemiainduced ARF in the present study. This was surprising given the number of previous studies that have demonstrated the protective effects of previous induction of HO-1 to limit renal damage after ischemia (19,20). The reason for this observation is unknown, but it is possible that because we did not detect a significant increase in HO activity by iCORM-3, the HO-1 induction failed to reach a significant threshold to afford protection against ischemia-induced ARF in the present study.…”
Section: Discussioncontrasting
confidence: 70%
“…The breakdown of heme by HO-1 leads to the production of the potent antioxidant bilirubin as well as the formation of Fe 3ϩ and CO gas. Several studies have demonstrated the protective effects of increased HO-1 activity in the kidney after ischemia (19,20); however, the precise mechanism by which increased HO-1 activity affords protection after ischemia has yet to be proved definitively. Because increased HO-1 activity is associated with an increase in bilirubin as well as CO production, it has not been possible to dissect out the contributions of each to the protective actions of HO-1 induction in the kidney after ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 induction occurs as an adaptive and benefi cial response to several injury processes, including oxidative injuries (Morimoto et al, 2001), rhabdomyolysis (Carstens et al, 2000), cisplatin nephrotoxicity and ARF (Shimizu et al, 2000). This may be explained by the generation of products from heme degradation, iron, carbon monoxide, biliverdin and bilirubin, which exert important antioxidant, antiinfl ammatory, and cytoprotective functions (Kirkby and Adin, 2006).…”
Section: Discussionmentioning
confidence: 99%